2007
DOI: 10.1007/s12038-007-0056-6
|View full text |Cite
|
Sign up to set email alerts
|

Basal transcription machinery: role in regulation of stress response in eukaryotes

Abstract: The holoenzyme of prokaryotic RNA polymerase consists of the core enzyme, made of two alpha, beta, beta' and omega subunits, which lacks promoter selectivity and a sigma (sigma) subunit which enables the core enzyme to initiate transcription in a promoter dependent fashion. A stress sigma factor sigma(s), in prokaryotes seems to regulate several stress response genes in conjunction with other stress specific regulators. Since the basic principles of transcription are conserved from simple bacteria to multicell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Similar accumulation of the TATA box has been observed in plants (Yamamoto et al 2011 ). A TATA box is a core element of the basal transcriptional machinery that regulates genes in conjunction with other cis -elements (Sadhale et al 2007 ). Consistent with these reports, our data demonstrated that TATA-box motifs affect the response to Fe deficiency in rice by collaborating with Fe deficiency-specific transcription factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar accumulation of the TATA box has been observed in plants (Yamamoto et al 2011 ). A TATA box is a core element of the basal transcriptional machinery that regulates genes in conjunction with other cis -elements (Sadhale et al 2007 ). Consistent with these reports, our data demonstrated that TATA-box motifs affect the response to Fe deficiency in rice by collaborating with Fe deficiency-specific transcription factors.…”
Section: Resultsmentioning
confidence: 99%
“…Downstream core elements (DCEs) were reported in yeast and mammalians downstream of TSSs, and are known to collaborate with the TATA box (Sadhale et al 2007 ). Some TATA box-binding protein (TBP)-associated factors (TAFs) bind to DCEs (Sadhale et al 2007 ). Our results showed that the DCEp1 (Figure 2 H) motif was commonly found immediately downstream of TSSs of Fe deficiency-inducible genes.…”
Section: Resultsmentioning
confidence: 99%
“…This core promoter region is often transcriptionally silent and with additional activating elements forms the minimal promoter for transcriptional efficiency. [Adapted from Smale and Kadonaga, 2003; Deng and Roberts 2006; Thomas and Chiang, 2006; and Sadhale et al, 2007. ]…”
Section: Figuresmentioning
confidence: 99%
“…GTFs are involved in formation of the pre-initiation complex that binds to the promoter region of DNA and regulates the basal transcriptional regulation [6]. On the other hand, GSTFs bind to sequences specific to certain genes and thus contribute to differential gene expression [7, 8].…”
Section: Introductionmentioning
confidence: 99%